Grafting of Polypyrrole-3-carboxylic Acid to the Surface of Hexamethylene Diisocyanate-Functionalized Graphene Oxide - José Antonio Luceño-Sánchez; Ana Maria Díez-Pascual (Nanomaterials, 2019)
A polypyrrole-carboxylic acid derivative (PPy-COOH) was covalently anchored on the surface of hexamethylene diisocyanate (HDI)-modified graphene oxide (GO) following two different esterification approaches: activation of the carboxylic acids of the polymer by carbodiimide, and conversion of the carboxylic groups to acyl chloride. Microscopic observations revealed a decrease in HDI-GO layer thickness for the sample prepared via the first strategy, and the heterogeneous nature of the grafted samples. Infrared and Raman spectroscopies corroborated the grafting success, demonstrating the emergence of a peak associated with the ester group. The yield of the grafting reactions (31% and 42%) was roughly calculated from thermogravimetric analysis, and it was higher for the sample synthesized via formation of the acyl chloride-functionalized PPy. The grafted samples showed higher thermal stability (~30 and 40 °C in the second decomposition stage) and sheet resistance than PPy-COOH. They also exhibited superior stiffness and strength both at 25 and 100 °C, and the reinforcing efficiency was approximately maintained at high temperatures. Improved mechanical performance was attained for the sample with higher grafting yield. The developed method is a valuable approach to covalently attach conductive polymers onto graphenic nanomaterials for application in flexible electronics, fuel cells, solar cells, and supercapacitors.